New discrete type inequalities and global stability of nonlinear difference equations - Udpin S. (2014)
In this work, we introduce discrete type inequalities. On the basis of these inequalities, we derive new global stability conditions for nonlinear difference equations. © 2008 Elsevier Ltd. All rights reserved.